Translation and psychometric evaluation of the Traditional Chinese eHealth Literacy Scale among adults with type 2 diabetes in Taiwan: A cross-sectional study - Yen-Ming Huang; Yu-Meng Yang; Tzu Wang; Hsun-Yu Chan (Digital Health)
Introduction The rise in online health information access has shifted health-seeking behaviors, yet a validated tool to assess eHealth literacy for the Taiwanese context remains unavailable. This study aimed to translate the eHealth Literacy Scale (eHEALS) into Traditional Chinese and validate its factor structure and reliability among individuals with type 2 diabetes (T2D). Methods The original 8-item eHEALS was translated into Traditional Chinese (eHEALS-TC) using forward and backward translation techniques, with input from four experts in pharmacy practice and educational psychology. A cross-sectional study was conducted to examine the validity and reliability of the eHEALS-TC in adults with T2D who were taking diabetes medication. Participants were recruited from five community pharmacies in Taiwan between June 2023 and May 2024. The internal consistency of the eHEALS-TC was assessed using McDonald's omega (ω), while construct validity was evaluated through exploratory factor analysis. Criterion validity was determined by exploring the correlation between the mean total eHEALS-TC score and demographic factors, self-efficacy, health status, medication adherence, and A1C levels. Results A total of 273 patients participated in the study. Exploratory factor analysis revealed that all eHEALS-TC items were loaded onto a single factor, accounting for 84.95% of the total variance. The internal consistency reliability yielded a McDonald's ω of 0.974. The mean total eHEALS-TC score was positively associated with younger age ( r  = .382, P  < .001), higher education attainment ( r s  = .525, P  < .001), greater household income ( r s  = .359, P  < .001), better self-reported health status ( r s  = .191, P  = .002), stronger self-efficacy in medication use ( r  = .167, P  = .006), and fewer barriers to medication-taking ( r  = .143, P  = .018). However, no association was found between the mean total eHEALS-TC score and A1C levels ( r  = .048, P  = .427). Conclusions The findings provide empirical evidence supporting the validity, reliability, and efficiency of the eHEALS-TC as a tool for assessing eHealth literacy among individuals with varying demographics and health conditions in Taiwan.